The impact of EFQM awards on organizational management - Pimentel, L. (2017)
Purpose: The purpose of this paper is to examine how the recognition of the European Foundation for Quality and Management (EFQM) awards to organizations (variable 1), particularly contribute to the improvement of management models, translated into different stages of evolution of management models/management control systems (variable 2), testing the hypothesis of correlation between these two variables. Methodology: The investigation covers the 35 organizations that won EFQM awards in Portugal (2010-2015). The bases are the different levels/scores of EFQM awards. Additionally, a questionnaire was used regarding the different stages of management models/management control systems (1=Basic stage of management control systems; 10=Advanced and very efficient management control systems stage). Moreover, interviews in all 35 organizations implied the collection of more accurate data. Findings: Important findings result from the research. Whenever organizations implement a quality management process/EFQM, substantial improvements occur in organizations regarding the implementation of management control models. Additionally, a positive and very strong correlation was found between the two variables: (i) different levels/scores of EFQM awards, and (ii) results of the questionnaire on different stages of management models/management control systems. Practical implications: The study makes it possible to conclude that the more an organization invests in a quality management process/program, the more efficient and useful a management control model becomes. Originality/Value: There is a gap in literature regarding the impact of quality management on the effectiveness of management models. Our study helps to close this gap, contributing to the development of a new body of knowledge, by assessing this favourable impact.